Wage Inequality: How and Why it has Changed over the Decades - Youngsun Koh (Korea Development Institute (KDI), 2019)
From 1980 to 2016, Korea exhibited ups and downs in wage inequality and a slowdown in wage growth. - Wage inequality fell in the 1st phase (1980-1994), rose in the 2nd (1995-2007), and fell again in the 3rd (2008-2016). - The annual growth rate of the real median wage plummeted from 9.2% in the 1st phase to 4.0% in the 2nd and then to 1.1% in the 3rd. - So far as wages are a form of compensation for the skills provided, wage inequality is affected by the changes in the supply of and demand for skills. - An important indicator of skill is the educational attainment of workers. The demand for high-school graduates rapidly increased in the 1st phase, weakening the wage premium of college graduates and reducing wage inequality. The situation reversed in the 2nd phase with a sharp upturn in the demand for college graduates, in their wage premium, and in wage inequality. In the 3rd phase, the wage premium of the latter dipped again as their supply continued amid the subdued demand for them. - The large demand for high-school graduates observed in the 1st phase may derive from the rising demand for mid-skilled workers by the heavy and chemical industry while the growing demand for college graduates observed in the 2nd phase may be the result of an increasing demand for high-skilled workers driven by technological progress. - To accelerate the wage growth while keeping wage inequality in check, technological progress should be encouraged and the quality of higher education upgraded.
Keywords: 330